Evolution and Trade-Off in the Multifunctional Cultivated Land System in Henan Province, China: From the Perspective of the Social-Ecological System - Niu, Pu; Zhou, Jiaxin; Yang, Yongfang; Xia, Yutian (Frontiers in Ecology and Evolution, 2022)
Cultivated land is a compound social-ecological system with the highest dependence on human beings. With changes in human demand, the function of the cultivated land system has undergone profound transformation. In this study, we analyze the development and evolution of cultivated land system functions, with the aim of providing decision-making support for national macro-management. Drawing on social-ecological system theory, and using multi-factor comprehensive analysis, ArcGIS spatial analysis, and a grey correlation model, this research evaluates the multifunctional temporal and spatial differences in the cultivated land system in 113 counties in Henan Province, China and analyzes their driving factors. The results show that: (1) the overall function of the cultivated system in Henan Province has obvious stage characteristics over the past 20 years, with the cultivated land function index being low from 1998 to 2013, and gradually increasing after 2013; (2) the trend of the cultivated land function has a progressive character, with the function index fluctuating from 0.3 to 0.6; (3) There is an obvious hierarchy among the sub-functions, showing the public role of production function, economic contribution function, employment guarantee function, food security guarantee function, and ecological security maintenance function; (4) Coordination analysis shows that there are trade-offs and synergies between sub-functions and the overall functions of the system; (5) Grey correlation analysis shows that urbanization, industrialization, agricultural modernization and agricultural policies play an important driving role in the evolution of cultivated land functions. These results not only provide a methodological and scientific basis for the evaluation, management and decision-making of cultivated land systems, but also provide a theoretical exploration of how the transformation of cultivated land goals can be integrated with sustainable development goals.